(untitled) (Journal of Forest and Livelihood, 2005)
The paper examines changes in livestock farming associated with community forestry (CF) in Nepal. Based on surveys of 259 households from 6 community forest user groups (CFUGs), and a survey of 64 CFUGs in three mid-hill districts in Nepal, the paper concludes that forage production and availability has decreased with the commencement of CF programs. This paper challenges the assumption that improved forest condition necessarily leads to improvement in livelihoods of the farmers.